Retroaortic Left Renal Vein in a Case of Left Adrenal Adenoma: Radiological Findings. (6th April 2011) - Dilli, Alper; Ayaz, Umit Yasar; Karabacak, Osman Raif; Hekimoglu, Baki
Abstract : It is important to diagnose retroaortic left renal vein (RLRV) before a probable retroperitoneal surgery in a case of a suspicious adrenal mass. Our purpose is to present the ultrasonography (US), computed tomography (CT), and magnetic resonance imaging (MRI) findings in a case of left adrenal adenoma with a coincidental RLRV and to discuss the clinical importance of their imaging. Abdominal and scrotal US, abdominal CT and MRI were performed for a 50-year-old male patient who was referred with continuous abdominal pain, intractable hypertension, high levels of blood cortisol and proteinuria. On US, a hypoechoic solid mass measuring 4 × 3 cm in the left adrenal location and coincidental RLRV, besides multiple renal cysts, hepatomegaly, left-sided varicocele, and small-sized left testis were detected. CT and MRI also revealed the mass in the left adrenal gland which was consistent with adenoma. With CT and MRI, presence of RLRV was also verified.